“Alas poor Yorick”: What retrospective analysis of canine skulls can tell us about the impact of environmental factors on health - Valenzuela, Luciano Oscar (2013)
Necropsies and extensive histological evaluation for clinical and sub-clinical disease of approximately three hundred Portuguese Water dogs are available as part of an ongoing study to assess their state of health at the end of life. Throughout life these dogs enjoyed a variety of lifestyles and environments. Here we carry out retrospective quantitative assessments of lifetime dietary input and physical activity for each dog. To do this, collagens from skull vault bone and from dentine have been analyzed for ratios of stable isotopes to determine differences in diet that individual dogs experienced during late or early life respectively. Robustness of skull bone (weight/unit of skull size) was used as a relative indicator of the amount of physical activity experienced during a dog’s lifetime. These environmental parameters were correlated with the frequency and severity of specific disease processes determined at necropsy. Both measures were shown to exert significant low-level (r < 25%) differential effects on specific diseases. The value of retrospective analysis of environmental influences is discussed.